Pengaruh Nilai Tukar Rupiah terhadap Neraca Perdagangan Indonesia Tahun 2021–2025 - Siti Uswatun Khasanah (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of the Indonesian Rupiah exchange rate on Indonesia's trade balance during the 2021–2025 period. The research employed a quantitative approach using monthly secondary data consisting of 60 observations of the Rupiah exchange rate (JISDOR) and Indonesia's trade balance. The data were obtained from Bank Indonesia and Statistics Indonesia and analyzed using simple linear regression with IBM SPSS Statistics. The results indicate that the Rupiah exchange rate has a regression coefficient of -0.156 with a significance value of 0.521 (>0.05), indicating that it does not have a significant effect on Indonesia's trade balance. Furthermore, the coefficient of determination (R²) is 0.007, meaning that the exchange rate explains only 0.7% of the variation in the trade balance, while the remaining 99.3% is influenced by other factors outside the research model. Therefore, Indonesia's trade balance is influenced not only by exchange rate fluctuations but also by various other economic factors.